(untitled) (VETERINARIA, 2020)
The field of pain management has profoundly evolved over the last decade. The International Association for the Study of Pain (IASP) defines pain as „an unpleasant sensory and emotional experience associated with actual or potential tissue damage or described in terms of such damage“. Adequate pain management should be a priority in veterinary surgery in terms of ethics, animal welfare, and reduce of morbidity and mortality. In veterinary medicine, scoring systems for pain rely on interpreting or measuring the consequences of pain. Results of numerous studies on pain support two treatment concepts, preventive and multimodal analgesia. Preventive analgesia includes analgesic application before occurrence of pain stimuli. Multimodal approach involves application of combination of two or more analgesics.